ANALYSIS OF THE PROMOTIONAL MIX IMPLEMENTATION IN ONE OF SMES IN BANDUNG CITY - A, Artarina D.; , Samoedra (CENTRAL ASIA AND THE CAUCASUS, 2022)
It is undeniable that the Covid-19 pandemic, starting from March 2020 until now, will impact all aspects of life, and one of them is the economic aspect. The wedding industry is a profitable business because of the demands from the bride and groom in preparing for their wedding. Facing the existing competition, as the entrepreneur that running companies must analyze the promotion mix. The method in this research is descriptive qualitative with case studies. The results obtained from the promotional mix carried out are advertising, sales promotion, and direct marketing. The main obstacle is the absence of particular costs for promotion and placement of appropriate human resources in the promotion mix arrangement, especially on social media. So, the solutions given are the placement of content admin staff for social media, making wedding packages more attractive, and making a particular budget for promotions, especially digital marketing.